PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA SAWIT POLA SWADAYA DI KECAMATAN KUBU KABUPATEN ROKAN HILIR - Bambang Sumantri; Rosnita '; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: (1) To identify the role of extension on independent small holder farmers of oil palm; (2) To know empowerment level of the farmers; (3) To analyze the aims of extension; (4) To analyze influence the role’s of extension toward empowerment and influence empowerment toward the aims of extension. This research is implemented in ‘Desa Teluk Merbau’ and ‘Desa Sungai Segajah Makmur’. Kubu Subdistrict, Rokan Hilir District. This research was conducted at Betung Village and Batang Kulim Village in Kubu Sub District Pelalawan District. Research’s respondent was determined by purposive sampling methods with number of respondent were 120. The location is chosen considering that there is a Counseling Institution, Active Counseling and Farmers Group. Validity, Realibility, Outliers, Normality, and Multikolinearity Analysis has been done on measuring treatment. To answer objectives number 1,2, and 3, use the “Scale Likert’s Summated Rating” (SLR) and to answer objectives numbr 4, use the “Strucutral Equation Modeling” with AMOS program. Research results shows: (1) Counseling role is very less in independent smallholder farmers of palm oil, that is viewed from counselour role giving education, information dissemination, facility, concultation, supervision, monitoring, and evaluation (2) farmers empowerment rates occur on less powerful level, viewed on human resources empowerment, productive economy, and institutions. (3) counseling objectives is sufficiently achieved that is viewed from better farming, better business dan better living; (4) role of counseling doesn’t influence directly toward farmers empowerment, and the farmer empowerment directly doesnt’s influence toward counseling objectives achievement. Key words:The role of extension, empowerments, extension aims, independent small holder, oil palm